2022
DOI: 10.1111/jfpe.14092
|View full text |Cite
|
Sign up to set email alerts
|

Flowability of spray‐dried sapodilla pulp powder

Abstract: This study aimed to evaluate the influence of maltodextrin, Arabic gum, and dextrin on phenolic compounds, morphology, and flowability of sapodilla pulp powder obtained in a spray dryer. Sapodilla pulp was characterized by its moisture and total polyphenols. The carriers were individually added to the pulp at a concentration of 20% (m/m), and the samples were dried in a spray dryer. The powders were analyzed for moisture, hygroscopicity, total polyphenols, and particle morphology, and their flowability was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…3M-P). Similar results were reported by Rajabi et al (2015) and Lima et al (2022) who worked on the microencapsulation of saffron extract and sapodilla pulp, respectively. Increasing GA concentration can enhance the powder yield by forming a more stable and viscous emulsion with the core material as it is capable of forming stable emulsion than MD alone, resulted in higher powder yield.…”
Section: -2-effect Of Wall Materials Proportions On the Microcapsulessupporting
confidence: 88%
See 1 more Smart Citation
“…3M-P). Similar results were reported by Rajabi et al (2015) and Lima et al (2022) who worked on the microencapsulation of saffron extract and sapodilla pulp, respectively. Increasing GA concentration can enhance the powder yield by forming a more stable and viscous emulsion with the core material as it is capable of forming stable emulsion than MD alone, resulted in higher powder yield.…”
Section: -2-effect Of Wall Materials Proportions On the Microcapsulessupporting
confidence: 88%
“…3A-D). Similarly, encapsulation of saffron extract (Rajabi et al, 2015), Sapodilla pulps (Lima et al, 2022), and lemongrass essential oil (Nguyen et al, 2022) using these biopolymers was reported. The water activity of samples exhibited different changes in SDM and FDM at both TS levels.…”
Section: -2-effect Of Wall Materials Proportions On the Microcapsulesmentioning
confidence: 84%
“…Starch powder flow was assessed by measuring its consolidation stress, unconfined yield stress, bulk density, and wall friction angles [28]. These measurements were carried out using Powder Flow Tester (PFT, Brookfield Engineering Labs, Essex, UK).…”
Section: Starch Flowabilitymentioning
confidence: 99%